Global economic and financial crisis: India's trade potential and future prospects - Prabir De (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2009)
This paper estimates the trade potential for India using the augmented gravity model and then attempts to determine the importance of trade remedies. Based on panel data, this gravity model is the first-ever attempt to estimate India's trade potential in the pre- and post- global economic and financial crisis period. The estimates of India's global trade potential reveal that the magnitude of India's trade potential is at its maximum in the Asia-Pacific region, followed by Africa and Latin America. Potential for expansion of trade in the post-crisis period is highest for countries such as China. However, in a large part of the world, India's trade has remained unrealized, which provides further opportunities to expand despite the slowdown in global demand. There is a strong complementary role, as the findings of this paper indicate; i.e., tariff liberalization and trade facilitation, which taken together can help build export momentum in the crisis period.
Keywords: 330; Außenwirtschaft; Gravitationsmodell; Finanzmarktkrise; Indien